2015
DOI: 10.1590/1807-3107bor-2015.vol29.0058
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effectiveness of Brazilian brown propolis against Enterococcus faecalis

Abstract: The aim of this study was to evaluate the in vitro antimicrobial activity of Brazilian brown propolis as an intracanal medication against Enterococcus faecalis. Thirty dentin discs prepared from intact freshly extracted bovine maxillary central incisors were infected with E. faecalis for 21 days. The specimens were distributed into six groups according to the medicament used as follows: G1-calcium hydroxide paste; G2-Carbowax 400 (control group); G3-20% brown propolis paste; G4-40% brown propolis paste; G5-20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
5
23
0
2
Order By: Relevance
“…It should be stressed that red propolis has been suggested to be the only propolis type derived from a plant from the Leguminosae family (D. ecastaphyllum), rich in isoflavones such as genistein and formononetin. Although flavonoids exhibit pleiotropic activity affecting several different targets, and synergistic effects cannot be ruled out, our results suggest that the isoflavone formononetin is responsible at least partially for the antimicrobial activity of red propolis 20 Bittencourt et al [30] Twenty-nine metabolites were identified along with 34 other metabolites that were classified into the following classes: triterpenoids (12), acetyltriterpenoids (3), sesquiterpenes (6), steroids (4), and hydrocarbons (9). The antioxidant capacity (IC50) ranged from 21.50 to 78.77 μg/mL, whereas the content of total phenolic compounds ranged from 31.88 to 204.30 mg GAE/g of dry weight.…”
Section: N°bibliographic Referencementioning
confidence: 73%
See 1 more Smart Citation
“…It should be stressed that red propolis has been suggested to be the only propolis type derived from a plant from the Leguminosae family (D. ecastaphyllum), rich in isoflavones such as genistein and formononetin. Although flavonoids exhibit pleiotropic activity affecting several different targets, and synergistic effects cannot be ruled out, our results suggest that the isoflavone formononetin is responsible at least partially for the antimicrobial activity of red propolis 20 Bittencourt et al [30] Twenty-nine metabolites were identified along with 34 other metabolites that were classified into the following classes: triterpenoids (12), acetyltriterpenoids (3), sesquiterpenes (6), steroids (4), and hydrocarbons (9). The antioxidant capacity (IC50) ranged from 21.50 to 78.77 μg/mL, whereas the content of total phenolic compounds ranged from 31.88 to 204.30 mg GAE/g of dry weight.…”
Section: N°bibliographic Referencementioning
confidence: 73%
“…Conclusions 09 Siqueira et al [19] The red propolis, collected in the region of Brejo Grande-SE, presents characteristics of identity and quality compatible with the parameters established by the Ministry of Agriculture and has proven effective against E. faecalis, being able, with more studies, to become a valuable endodontic treatment 10 Pimenta et al [20] The present study demonstrated that, although medications based on brown propolis with or without calcium hydroxide have limitations inherent to an in vitro study, they are effective against E. faecalis 11 Siqueira et al [21] The results of this study show that, similar to chlorhexidine, red propolis alcoholic extract has good fungistatic and fungicidal activity against most samples of Candida species. This antifungal activity may hold a promise for future applications as an alternative treatment for infections caused by these fungi.…”
Section: N°bibliographic Referencementioning
confidence: 87%
“…aromatic aldehydes and alcohols, fatty acids, stilbenes, and β-steroids. The use of propolis as a root canal medicament have been suggested (1,4,7,8,9,10,11,12,13). The aim of the present study is to test the antibacterial effect of propolis and to compare it with bench mark materials as Ca(OH)2 and CHX.…”
Section: Discussion:-mentioning
confidence: 98%
“…Propolis is mainly effective against grampositive bacteria (4). So, its use in endodontic treatment is of great importance especially against Enterococcus faecalis (1,3,12,13).…”
mentioning
confidence: 99%
“…(Dianat et al, 2015) and the intra-canal administration of calcium hydroxide, camphorated paramonochlorophenol-(CMCP), formocresol, tricresol formalin and/or a combination of corticosteroid and antibiotics. Given these limitations and based on the traditional use and relative ease of the isolation of active components, plants may provide potential sources of new drugs for the safe and effective treatment of diseases (Santos et al, 2008;Pimenta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%